FITRAH PERSPEKTIF HADITH: STUDI KRITIK SANAD, MATAN, DAN PEMAHAMANNYA - Erwati Aziz (UIN Raden Mas Said Surakarta, 2017)
This research aims to describe the conception of fitrah in the perspective of hadith. This is qualitative research, in which the data gathered from the various correlated literature to the focus of the study, such as Alqur’an and Hadith and the other religious texts. Takhrij is necessary conducted in order to know the credibility of rawi and the authenticity of hadith, followed by cross-checking to the qur’anic verses which are in line with the text of hadith in order to find out the comprehensive understanding. Hereby, the result of the research revealed that hadith-hadith which is talking about fitrah discussed, judged as maqbul and representative to be used as hujjah, or fundamental concept of fitrah and it is able to be implemented into the daily life.